MAKNA SIMBOLIK SUNDA WIWITAN DALAM TRADISI MEUNGKEUT BUMI - Yayang Dwi; Ranti Pebrianti Ranti; Dede Fatimah Deffa; Zikri Fachrul Nurhadi (Prodi Ilmu Komunikasi Universitas Putera Batam, 2023)
This research is motivated by problems from culture in the beliefs of Sunda Wiwitan which require the existence of the